Declining Use of Corticosteroids for Crohn's Disease Has Implications for Study Recruitment: Results of a Pilot Randomized Controlled Trial. Issue 5 (20th November 2020) - Balart, M T; Russell, L; Narula, N; Bajaj, G; Chauhan, U; Khan, K J; Marwaha, A N; Ching, E; Biro, J; Halder, S; Tse, F; Marshall, J K; et al.
Abstract: Background: Corticosteroids (CS) have been used extensively to induce remission in Crohn's disease (CD); however, they are associated with severe side effects. We hypothesized that the administration of an exclusive enteral nutrition (EEN) formula to CS would lead to increased CD remission rates and to decreased CS-related adverse events. We proposed to undertake a pilot study comparing EEN and CS therapy to CS alone to assess decrease symptoms and inflammatory markers over 6 weeks. Aim: The overall aim was to assess study feasibility based on recruitment rates and acceptability of treatment in arms involving EEN Methods: The pilot study intended to recruit 100 adult patients with active CD who had been prescribed CS to induce remission as part of their care. The patients were randomized to one of three arms: (i) standard-dose CS; (ii) standard-dose CS plus EEN (Modulen 1.5 kcal); or (iii) short-course CS plus EEN. Results: A total of 2009 CD patients attending gastroenterology clinics were screened from October 2018 to November 2019. Prednisone was prescribed to only 6.8% (27/399) of patients with active CD attending outpatient clinics. Of the remaining 372 patients with active CD, 34.8% (139/399) started or escalated immunosuppressant or biologics, 49.6% (198/399) underwent further investigation and 8.8% (35/399) were offered an alternative treatment (e.g., antibiotics, surgery or investigational agents in clinical trials). Only three patients were enrolled in the study (recruitment rate 11%; 3/27), and the study was terminated for poor recruitment. Conclusion: The apparent decline in use of CS for treatment of CD has implications for CS use as an entry criterion for clinical trials.